2012
DOI: 10.3174/ajnr.a2907
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Diverter Silk Stent for the Treatment of Intracranial Aneurysms: 1-year Follow-Up in a Multicenter Study

Abstract: BACKGROUND AND PURPOSE: FD stent placement is a promising therapy for challenging intracranial aneurysms. Long-term evaluations about angiographic and morphologic results are still missing. This is the aim of this multicenter series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
142
1
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(170 citation statements)
references
References 22 publications
16
142
1
11
Order By: Relevance
“…However unknown the mechanism leading to these hemorrhages remains, some factors such as hemorrhagic transformation and use of anti-platelet are alleged as guilty culprits (16)(17)(18). No intraparenchymal hemorrhages were observed in our study although the rates of the hemorrhages were reported to range between 0% and 10% in several studies (16)(17)(18).…”
Section: Discussioncontrasting
confidence: 52%
“…However unknown the mechanism leading to these hemorrhages remains, some factors such as hemorrhagic transformation and use of anti-platelet are alleged as guilty culprits (16)(17)(18). No intraparenchymal hemorrhages were observed in our study although the rates of the hemorrhages were reported to range between 0% and 10% in several studies (16)(17)(18).…”
Section: Discussioncontrasting
confidence: 52%
“…Recently, several flow-diverter stents, such as the Silk flow diverter (Balt Extrusion, Montmorency, France), have been released, and short-and midterm results have been published. [7][8][9][10][11][12][13][14][15] Notwithstanding the early promise of these devices, important shortcomings have been reported. First, delayed complications, either hemorrhagic or thromboembolic, are not uncommon; second, the flow-diverter stent tolerance might be considered poor because of the relatively high rates of intrastent stenosis and parent artery occlusion (PAO) during follow-up.…”
Section: -4mentioning
confidence: 99%
“…First, delayed complications, either hemorrhagic or thromboembolic, are not uncommon; second, the flow-diverter stent tolerance might be considered poor because of the relatively high rates of intrastent stenosis and parent artery occlusion (PAO) during follow-up. [7][8][9][10][11][12][13][14][15] To the best of our knowledge, sparse data are available about the long-term results of this technique, including stability of aneurysm occlusion and stent tolerance. These data are mandatory to define the place of flow-diverter stents in the therapeutic armamentarium of intracranial aneurysms.…”
Section: -4mentioning
confidence: 99%
See 1 more Smart Citation
“…Studien zeigten sich In-Stent-Thrombosen oder -stenosen in 18 -33 % der berichteten Fälle nach 6 Monaten [7,10] …”
unclassified